Answer:
4x² -29x +51
Step-by-step explanation:
Put x-3 where x is in the original function definition, then "simplify". I think you'll find it convenient to rewrite the original function definition first.
... g(x) = 4x² -5x = x(4x -5)
Substituting, we have
... g(x-3) = (x -3)(4(x -3) -5)
... = (x -3)(4x -17) . . . . . simplify right factor
... = 4x² -12x -17x +51
... g(x -3) = 4x² -29x +51
12 = 12/1 = 24/2, 24/2+1/2=25/2 so 25/2, and it's in simplest form because 2 can't go into 25
Answer:
i believe it is (3,6) im not 100% sure though
Step-by-step explanation:
Subtract 8 from both sides to get y = 8 as your final answer.
Answer:
PLEASE CHECK OUT SUPERNATURAL THE SHOW
Step-by-step explanation:
DEAN X CASS THE ANGEL = LOVE
BEST SHOW EVER